2015
DOI: 10.18092/ijeas.48129
|View full text |Cite
|
Sign up to set email alerts
|

Dönüşümcü Ve Etki̇leşi̇mci̇ Li̇derli̇k İle Öğretmenleri̇n Tükenmi̇şli̇k Düzeyleri̇ Arasindaki̇ İli̇şki̇

Abstract: Bu çalışma okul yöneticilerinin sahip oldukları liderlik tarzlarının öğretmenlerin bakış açılarıyla ortaya konularak, yöneticilerin sergiledikleri liderlik davranışları ile öğretmenlerin tükenmişlik düzeyleri arasındaki ilişkiyi incelemek amacıyla yapılmıştır. Elde edilen bulgular doğrultusunda dönüşümcü, etkileşimci ve serbest bırakıcı liderlik tarzlarından okul yöneticilerinin en çok serbest bırakıcı liderlik daha sonra ise sırası ile etkileşimci ve dönüşümcü liderlik davranışlarını sergiledikleri bulgusuna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
2
Order By: Relevance
“…Gövez [63] found that transformational and transactional leadership decreased the level of cynicism, while transformational leadership model affected (decreased) cynicism level more. In their study on the effect of school managers' leadership styles on exhaustion, Bakan [64] concluded that school managers showed laissez-faire leadership style the most, followed by transactional and transformational leadership behaviours. The second sub-problem of the study was "What is the level of teachers' organizational cynicism perceptions?"…”
Section: Discussionmentioning
confidence: 99%
“…Gövez [63] found that transformational and transactional leadership decreased the level of cynicism, while transformational leadership model affected (decreased) cynicism level more. In their study on the effect of school managers' leadership styles on exhaustion, Bakan [64] concluded that school managers showed laissez-faire leadership style the most, followed by transactional and transformational leadership behaviours. The second sub-problem of the study was "What is the level of teachers' organizational cynicism perceptions?"…”
Section: Discussionmentioning
confidence: 99%
“…Many studies can be found in the Turkish context with regard to teacher burnout. In these studies, teacher burnout was examined in relation to teacher self-efficacy (Cansoy, Parlar & Kılınç, 2017;Saricam & Sakiz, 2014), administrators' leadership styles (Bakan, Erşahan, Büyükbeşe, Doğan & Kefe, 2015), emotional labour (Akın, Aydın, Erdoğan & Demirkasımoğlu, 2014), job-life satisfaction (Avşaroğlu, Deniz & Kahraman, 2005), depression, job satisfaction, mobbing (Aydoğan, Doğan & Bayram, 2009;Çınar, 2015;Ertürk & Keçecioğlu, 2012;Gençay, 2007;Okçu & Çetin, 2017), ideologies of student control (Bas, 2011), subjective well-being and school life quality (Cenkseven Önder & Sarı, 2009), principals' service-oriented leadership behaviours (Cerit, 2008), organisational trust (Çağlar, 2011), organisational commitment (Çetin, Basım & Aydoğan, 2011, professional competence (Çiftçi, 2015), psychological endurance and self-monitoring (Erkutlu, 2012), collective efficacy and self-regulation (Gürçay, Yılmaz & Ekici, 2009), organisational citizenship (İnandı & Büyüközkan, 2013), students' in-class misbehaviour (Karakaya, Brusseau & Karademir, 2015), emotional intelligence and stress (Karakuş, 2013), psychological violence, stress and life satisfaction (Karakuş & Çankaya, 2012), job satisfaction and locus of control (Sari, 2005;Savaş, Bozgeyik & Eser, 2014;Sünbül, 2003), organisational citizenship behaviours (Sezgin & Kılınç, 2012), being a learner organisation (Çam-Tosun & Altunay, 2017) and professional commitment (Tümkaya & Uştu, 2016). e-ISSN: 2536-4758 http://www.efdergi.hacettepe.edu.tr/…”
Section: Introductionmentioning
confidence: 99%
“…This culture is similar to the Harrison's existential culture. The idea is that organizations are for the individuals therefore, the outstanding purpose of organizations is to promote the well being and happiness of the individuals (Bakan, Büyükbeşe, & Bedestenci, 2004).…”
Section: Organizational Culturementioning
confidence: 99%
“…This type of culture is similarly structured with the Harrison's task culture. This approach is based on organizational goals mainly centralized in task or work (Bakan, Büyükbeşe, & Bedestenci, 2004). Support culture is formed by different task groups and each group has expertise in its own area.…”
Section: Support Culturementioning
confidence: 99%